Water stress in plants: a review (Research, Society and Development, 2021)
Water stress is a problem that limits the production and development of various plants, especially in dry periods where the river index is lower. This review compiles information that allows us to understand how stress due to lack of water occurs, a resource of extreme importance for plant development, with water being an extremely determining component for the survival of plants, being responsible for gas exchange, photosynthesis, transport of nutrients and others. Thus, given the data obtained in the research platforms Google academic, Scielo, Embrapa and others, we discuss the responses of fruit, forage and legume plants subjected to water stress, highlighting the effects caused in general and mentioning some of the peculiarities that stress causes in these plants, in addition to the means of adaptation that these plants acquire to survive during periods of drought and how water is important at various stages of plant development.